MODELISASI KURSI DENGAN PENGGABUNGAN HASIL DEFORMASI BENDA-BENDA RUANG MENGGUNAKAN KURVA BEZIER - Nadzira, Annisa Ayu; Juliyanto, Bagus; Kamsyakawuni, Ahmad (Jurusan Matematika FMIPA Universitas Jember, 2021)
Chairs are needed by humans to do some work, especially students and office workers. The parts contained in the chair are the chair legs, chair legs eats and chair backs. The purpose of this study is to obtain variations in the shape of office chairs using Bezier curves and incorporate the results of deformation of space geometric objects. In modeling this chair, it is divided into several stages, namely first, building the chair leg components. This chair leg component consists of chair wheels, connecting two wheels with tube deformation, modeling the chair leg branch components and modeling chair leg supports. Second, namely the model of the chair leg seat. Chair leg seat consists of regular hexagon prism deformation and regular quadrangle prism deformation. The third is the modelization of the back of the chair by using a rectangular prism model. The result of combining several components of the chair using one modeling axis produces 36 chair models, with special provisions, namely that the seat support parts can only be joined using a tube.